2023
DOI: 10.1088/2058-6272/acd74b
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of phase modulation and propagation-route effect from unmatched large-scale structures for Doppler reflectometry measurement through 2D full-wave modeling

Abstract: To interpret the common symmetric peaks caused by the large-scale structure in the complex S(f) spectrum from the heterodyne Doppler reflectometry (DR) measurement in EAST, a 2D circular-shape O-mode full wave model based on the finite-difference time-domain method is built. The scattering characteristics and the influences on the DR signal from various scales are investigated. When the structure is located around the cut-off layer, a moving radial or poloidal large scale structure $k_\theta\lesssim k_{\theta,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…From figure 9, as the radiation increasing, the turbulence intensity and the absolute values of T e gradient inside MI all increased, while only the T e gradient at X-point remained almost unchanged. It should be noted that although the ray tracing in figure 5(a) suggested that the turbulence measurement location is at the inner side of MI (positive R 0 /L Te ), the possibility that turbulence may trigged by the inverted R 0 /L Te could not be ruled out, because that turbulence spreading [29,30] and DR measurement principle [31][32][33] should both be considered. So, the relationships between turbulence amplitude and positive R 0 /L Te and inverted R 0 /L Te are both plotted in panel (d).…”
Section: Turbulence Drivenmentioning
confidence: 99%
“…From figure 9, as the radiation increasing, the turbulence intensity and the absolute values of T e gradient inside MI all increased, while only the T e gradient at X-point remained almost unchanged. It should be noted that although the ray tracing in figure 5(a) suggested that the turbulence measurement location is at the inner side of MI (positive R 0 /L Te ), the possibility that turbulence may trigged by the inverted R 0 /L Te could not be ruled out, because that turbulence spreading [29,30] and DR measurement principle [31][32][33] should both be considered. So, the relationships between turbulence amplitude and positive R 0 /L Te and inverted R 0 /L Te are both plotted in panel (d).…”
Section: Turbulence Drivenmentioning
confidence: 99%